Calibration of Geomagnetic and Soil Temperatur Sensor for Earthquake Early Warning System - Dodi Yudo Setyawan; Dona Yuliawati; Warsito Warsito; Warsono Warsono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The study of Design of Earthquake Early Warning System for Real Time Using Geomagnetism and Total Electron Content with Fuzzy Logic through competitive grants scheme has obtained the prototype of the earthquake early warning system. However, it still needs improvements on in the calibration of thesensor system especially for MAG3110 sensor and DHT11 sensor. This calibration was done by adjusting the sensor system to the existing measuring devices standards in the Physics Department laboratory of the Sains Faculty Lampung University, to obtain measurement accuracyand to get a good result about where and when the earthquake would occurand how strong the earthquake would be. The calibration of MAG3110 sensor and DHT11 sensor obtained the standard correction results, the standard deviation of MAG3110 from 3 axes, namely x axis was 8.5, y axis was 2.66, and z axis was 1.9, whereas the standard deviation for DH11 sensor was 0.1161.